Production and marketing factors influencing fed cattle prices - Mintert, J.; Jones, R.; Brazle, F.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An analysis of more than 1400 pens of cattle marketed during 1990 examined the influence of several cattle traits and marketing factors on fed cattle prices. Cattle quality grade had an important impact on packer bids and feedyard asking prices. However, both feedyard asking and packer purchase prices reflected less than 25%, on average, of estimated wholesale value differentials. Other factors, including estimated dressing percentage, finish uniformity, cattle weight, number of head purchased, presence of heiferettes, and cattle type had significant price impacts. Feedyards generally received what they asked for cattle; 65% of the pens sold for their asking prices. Price signals for differences in cattle "quality" are not fully transmitted to cattle feeders.
Keywords: Beef; Cattle marketing; Cattle prices; Cattle values